PERLINDUNGAN HAK EKONOMI DAN HAK MORAL ATAS KARYA CIPTA DI BIDANG FOTOGRAFI TERKAIT DOKTER SEBAGAI MODEL IKLAN RUMAH SAKIT (STUDI PUTUSAN NOMOR 262K/PDT.SUS-HKI/2016) - Rico Daniel; Suyud Margono (Fakultas Hukum Universitas Tarumanagara, 2020)
Siloam Hospitals Surabaya has violated the law regarding Article 12 of the UUHC. The problem faced in writing this thesis is how to protect economic rights and moral rights of copyrighted works in the field of photography related to doctors as a model of hospital advertising (Decision Study Number 262K / Pdt.Sus-HKI / 2016). The research method used in writing this thesis is normative legal research. The results showed that the protection of economic rights and moral rights of copyrighted works in the field of photography related to doctors as a model of hospital advertising, especially in Decision Number 262K/Pdt.Sus-HKI 2016, in which case the protection is automatic when the idea is realized in concrete / concrete form, the work has been protected and of course without requiring recording (both recorded and undocumented). So based on this it is clear that in order to obtain Copyright protection, a photographic work of art does not need to pass the registration stage first, because automatically after the work is manifested in a tangible form and exhibited to the general public, then the work has obtained Copyright recognition and is protected Copyright and if registration is carried out, then it is done solely for the purpose of proving if a dispute later arises in relation to Copyright for the photos and copyright protection for photographic works of art is given to protect the rights of an Author namely economic rights and moral rights.